On Neutrosophic Normed Spaces of I-Convergence DiferenceSequences Defned by Modulus Function - Vakeel A. Khan; Mohammad Arshad (Neutrosophic Sets and Systems)
In this paper, we introduce the neutrosophic I-convergent difference sequence spaces I(Y) (∆) (f ) and I0(Y) (∆) (f ) defined by modulus function. Also, we define an open ball B(x, ϵ, γ)(f ) in neutrosophic norm space defined by modulus function. Furthermore, We construct new topological spaces and look into various topological aspects in neutrosophic I-convergent difference sequence spaces I(Y) (∆) (f ) and I0(Y) (∆) (f ) defined by modulus function.